2003
DOI: 10.2337/diabetes.52.4.918
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the Deterioration in Glucose Tolerance Associated With HIV Protease Inhibitor Regimens

Abstract: The mechanisms responsible for the deterioration in glucose tolerance associated with protease inhibitorcontaining regimens in HIV infection are unclear. Insulin resistance has been implicated as a major factor, but the affected tissues have not been identified. Furthermore, ␤-cell function has not been evaluated in detail. The present study was therefore undertaken to assess the effects of protease inhibitor-containing regimens on hepatic, muscle, and adipose tissue insulin sensitivity as well as pancreatic ␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
1
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 48 publications
4
122
1
4
Order By: Relevance
“…Metabolic side-effects may occur in up to 60% of HAART-treated patients, depending on host factors (presence of "traditional" risk factors for Type 2 diabetes) and on the specific agents used in the cocktail [3,4]. Further clinical and pharmacological studies have identified the HIV protease inhibitors as a class of agents that may independently contribute to the development of peripheral insulin resistance [5], as well as to impaired pancreatic beta cell function [6]. Yet adipose tissue alterations appear to lie at the centre of this metabolic syndrome, since it is frequently associated with adipose tissue redistribution, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic side-effects may occur in up to 60% of HAART-treated patients, depending on host factors (presence of "traditional" risk factors for Type 2 diabetes) and on the specific agents used in the cocktail [3,4]. Further clinical and pharmacological studies have identified the HIV protease inhibitors as a class of agents that may independently contribute to the development of peripheral insulin resistance [5], as well as to impaired pancreatic beta cell function [6]. Yet adipose tissue alterations appear to lie at the centre of this metabolic syndrome, since it is frequently associated with adipose tissue redistribution, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…lipodystrophy of subcutaneous "peripheral" adipose tissue, but an increase in abdominal adipose mass (central adiposity) [5,7,8]. Furthermore, impaired glucose tolerance and dyslipidaemia frequently occur, with elevated circulating levels of non-esterified fatty acids signifying abnormal regulation of adipocyte lipid metabolism [6]. Thus, a striking clinical similarity exists between common forms of the insulin resistance syndrome and this newly identified drug-induced metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…glucose is a very sensitive index of b-cell function compared with the insulin response to non-glucose secretagogues (45). The aetiology of the islet b-cell dysfunction in HIV-lipodystrophy is not known, but a hypothesis focusing on a deleterious effect of HAART on b-cell function has been discussed (7,46). A defect in the incretin signalling may also explain the b-cell dysfunction (47).…”
Section: Substrate Metabolismmentioning
confidence: 99%
“…The major phenotypic trait of HIV-associated lipodystrophy syndrome (HALS) is loss of extremity fat including facial and gluteal regions and fat gain in the trunk region (2). Metabolically, the syndrome is characterized by insulin resistance (3,4), impaired glucose tolerance (5,6) and hepatic insulin resistance (7). Also, fat metabolism is disturbed with reports on increased lipolysis (8), increased fat deposition in the liver (9) and muscle tissue (10,11), increased expression of tumour necrosis factor-a in fat tissue and decreased plasma levels of adiponectin (12).…”
Section: Introductionmentioning
confidence: 99%
“…16 A clinical report revealed glucose intolerance and insulin resistance in HIV-positive patients treated with HPIs. 17 Moreover, the incidence of insulin resistance in HIV-positive patients is significantly higher in HPI-treated patients than in patients treated with NRTIs or NNRTIs, 18 even when one considers related factors such as demography and virology. 19 Furthermore, HPIs have been shown to induce insulin resistance in seronegative patients and in animal models, [20][21][22][23] implying a clear link between HPI use and insulin resistance.…”
Section: Insulin Resistance and Hiv Protease Inhibitors (Hpis)mentioning
confidence: 99%